Direct observation of spin diffusion enhanced nonadiabatic spin torque effects in rare-earth-doped permalloy - Krautscheid, Pascal; Reeve, Robert M.; Schoenke, Daniel; Boventer, Isabella; Conca, Andres; Chumak, Andrii; Hillebrands, Burkard; Ehrler, Jonathan; Osten, Julia; Fassbender, Juergen; Klaeui, Mathias (Physical Review B, 2018)
The relation between the nonadiabaticity parameter β and the damping parameter α is investigated in permalloy-based microdisks. In order to determine β, high-resolution imaging of the current-induced vortex-core displacement is performed using scanning electron microscopy with polarization analysis. The materials properties of the films are varied via rare-earth Dy doping, leading to a greatly enhanced damping, while retaining the same spin configuration for the confined vortex state. A clear trend to much higher nonadiabaticity values is seen for the higher doping levels and an averaged value of β=(0.29±0.15)×10-2 is determined for 1.73% Dy doping, compared to (0.067±0.014)×10-2 which is extracted for pure permalloy. This is supportive of a similar scaling of β and α in this system, pointing to a common origin of the spin relaxation which is at the heart of nonadiabatic transport and the dissipation of angular momentum that provides damping, in line with theoretical calculations.
CRIS-Team Scopus Importer:2023-03-27